2018
DOI: 10.14716/ijtech.v9i4.1808
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of the Period of Saccharification on Oil Palm (Elaeis guineensis) Trunk Sap Hydrolysis

Abstract: This study investigates the enzymatic hydrolysis rate of Oil Palm (Elaeis guineensis) Trunk (OPT) sap in terms of the length of saccharification process with the aim to elevate sugar production. Emphasis was placed on the reaction time and addition of supplements such epsom salt (MgSO4) and alanine amino acid (C3H7NO2) to accelerate the efficiency of Saccharomyces cerevisiae containing the enzyme invertase. A whole oil palm trunk was divided into four different sections, upper, middle-1, middle-2 and bottom wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…It can be concluded that S. cerevisiae still has not consumed a large amount of glucose content inside the solution. A previous saccharification study from oil palm trunk (OPT) demonstrated that Epsom salt (MgSO 4 ) and alanine amino acid (C 3 H 5 NO 2 ) addition, during hydrolysis increased the sugar yield from 12.52% to 17.19% [27]. Hence, additional supplements, such as vitamin B 12 , Epsom salt, alanine amino acid, and other vitamins-minerals, as well as recombinant yeast and yeast strains to the fermentation solution, are highly recommended for further experiments to obtain desired sugar content [43].…”
Section: Glucose and Biomass Content Analysis During Fermentation Promentioning
confidence: 99%
See 3 more Smart Citations
“…It can be concluded that S. cerevisiae still has not consumed a large amount of glucose content inside the solution. A previous saccharification study from oil palm trunk (OPT) demonstrated that Epsom salt (MgSO 4 ) and alanine amino acid (C 3 H 5 NO 2 ) addition, during hydrolysis increased the sugar yield from 12.52% to 17.19% [27]. Hence, additional supplements, such as vitamin B 12 , Epsom salt, alanine amino acid, and other vitamins-minerals, as well as recombinant yeast and yeast strains to the fermentation solution, are highly recommended for further experiments to obtain desired sugar content [43].…”
Section: Glucose and Biomass Content Analysis During Fermentation Promentioning
confidence: 99%
“…Table 4 shows that the pure bioethanolic yield was 0.25 mL/mL fermented solution or 25%. After obtaining distilled bioethanol, the left-over solution may contain unfermented sugars, by-products (heavy alcohols, aldehydes, and others), Na 2 SO 4 , water, lignin, and gaseous components: CO 2 and CH 4 [27,45]. The bioethanol of banana stem grown in Malaysia was higher than the highest leading feedstock for bioethanol of the country, oil palm trunk (OPT).…”
Section: Pure Bioethanol After Distillationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent world, energy turned into a key driving force has been researched for enhancing optimized usages and generating renewable sources due to tremendous depletion of fossil fuel and threatening greenhouse effects . In this regard, the alternative source of energy generation became a crucial concept to be considered.…”
Section: Introductionmentioning
confidence: 99%